2008
DOI: 10.1152/ajpheart.00823.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of 5,6,7,8-tetrahydrobiopterin to 7,8-dihydrobiopterin in endothelial cells determines glucose-elicited changes in NO vs. superoxide production by eNOS

Abstract: Crabtree MJ, Smith CL, Lam G, Goligorsky MS, Gross SS. Ratio of 5,6,7,8-tetrahydrobiopterin to 7,8-dihydrobiopterin in endothelial cells determines glucose-elicited changes in NO vs. superoxide production by eNOS. Am J Physiol Heart Circ Physiol 294: H1530-H1540, 2008. First published January 11, 2008 doi:10.1152/ajpheart.00823.2007 is an essential cofactor of nitric oxide synthases (NOSs). Oxidation of BH4, in the setting of diabetes and other chronic vasoinflammatory conditions, can cause cofactor insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
193
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(206 citation statements)
references
References 65 publications
11
193
1
1
Order By: Relevance
“…Moreover, NO has also been shown to stimulate glutathiolation of a specific protein which results in cyclic guanosine monophosphate-independent arterial relaxation (Cohen and Adachi 2006). Recent studies suggest that the biopterin red-ox status is more important to the activity of NOS than the total amount of biopterin and that GSH contributes to maintain this ratio (Crabtree et al 2008(Crabtree et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NO has also been shown to stimulate glutathiolation of a specific protein which results in cyclic guanosine monophosphate-independent arterial relaxation (Cohen and Adachi 2006). Recent studies suggest that the biopterin red-ox status is more important to the activity of NOS than the total amount of biopterin and that GSH contributes to maintain this ratio (Crabtree et al 2008(Crabtree et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…When BH4 availability is limiting, electron transfer from NOS flavins becomes uncoupled from L-arginine oxidation, eNOS generates superoxide rather than NO, BH4 becomes oxidized to catalytically incompetent BH2, and a futile feed-forward cascade of BH4 destruction proceeds (1). Recent studies reveal that BH4 and BH2 bind eNOS with equal affinity and that BH2 can efficiently replace eNOS-bound BH4, resulting in eNOS uncoupling (6). Indeed, we have previously shown that the relative abundance of eNOS versus BH4 together with the intracellular BH4:BH2 ratio, rather than absolute concentrations of BH4, are the key determinants of eNOS uncoupling (7), a hypothesis supported by a recent publication where BH2 levels are elevated after exposure of bovine aortic endothelial cells to DHFR-specific siRNA (8).…”
mentioning
confidence: 99%
“…Normally, the vascular endothelium facilitates blood flow principally by releasing endothelial-derived nitric oxide (NO) via vascular endothelial NO synthase (eNOS) in the presence of an essential co-factor, tetrahydrobiopterin (BH4). By contrast, acute and chronic hyperglycemia increase oxidative stress and reduce NO bioavailability [1,2]. The reduced endothelial-derived NO bioavailability promotes vasoconstrictive, pro-inflammatory, and pro-thrombotic events, initiating inflammation, thereby recruiting leukocytes, resulting in tissue/organ damage ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduction of oxidative stress during hyperglycemia will mitigate vascular endothelial dysfunction and organ damage. Crabtree, et al [1] found that mitochondria-derived superoxide (SO) contributes to hyperglycemia-induced oxidative stress in cultured vascular endothelial cells. Subsequently, the overproduction of SO promotes the oxidation of BH4 to dihydrobiopterin (BH2).…”
Section: Introductionmentioning
confidence: 99%